HIV-associated neurocognitive disorders in Africa: challenges, peculiarities, and future directions - Tobi Olajide; Evelyn Ogungbemi; Gideon Olajide; Deborah Ogundijo; Oluwanifemi Osakuade; Favour Moshood (AIDS Research and Therapy)
Abstract The impact of Human Immunodeficiency Virus (HIV) on neurocognition in Africa is a pressing public health issue, with profound implications for both individual well-being and healthcare systems across the continent. This narrative review aims to elucidate the intricate relationship between HIV infection and neurocognitive function, particularly focusing on HIV-associated neurocognitive disorders (HAND), the effects of antiretroviral therapy (ART), and neuropathological changes. Evidence from Africa emphasizes the variability in the prevalence of neurocognitive impairment among people living with HIV. For instance, a meta-analysis showed that Central and South Africa had the highest pooled prevalence of neurocognitive impairment (NCI) (49.33%), followed by East Africa (45.04%) and West Africa (42.40%). These differences may reflect varying ART coverage, healthcare infrastructure, and the prevalence of co-infections like tuberculosis highlighting the importance of region-specific interventions and support services tailored to local contexts. Furthermore, challenges such as late diagnosis, methodological variations, treatment non-adherence, and limited access to specialized care exacerbate the burden of neurocognitive impairment in this setting. Addressing the complex intersection of HIV and neurocognition in Africa requires a multifaceted approach involving various stakeholders, including healthcare providers, policymakers, researchers, and community organizations. Enhancing awareness, education, and capacity- building initiatives can improve early detection and management of neurocognitive disorders among individuals living with HIV. Moreover, investment in infrastructure and resources for neurocognitive care, including diagnostic tools and rehabilitation services, is essential to meet the growing needs of this population. Additionally, promoting research collaboration and knowledge exchange is important for advancing our understanding of HIV-related neurocognitive impairment and developing evidence-based interventions. By fostering partnerships between academia, healthcare institutions, and governmental agencies, we can facilitate the translation of research findings into policy and practice, ultimately improving outcomes and quality of life for individuals affected by HAND in Africa.